1995
DOI: 10.1073/pnas.92.18.8358
|View full text |Cite
|
Sign up to set email alerts
|

Radiometal labeling of recombinant proteins by a genetically engineered minimal chelation site: technetium-99m coordination by single-chain Fv antibody fusion proteins through a C-terminal cysteinyl peptide.

Abstract: We describe a method to facilitate radioimaging with technetium-99m (99mTc) by genetic incorporation of a 99mTc chelation site in recombinant single-chain Fv (sFv) antibody proteins. This method relies on fusion of the sFv C terminus with a Gly4Cys peptide that specifically coordinates 99mTc. By using analogues of the 26-10 anti-digoxin sFv as our primary model, we find that addition of the chelate peptide, to form 26-10-1 sFv', does not alter the antigen-binding affinity of sFv. We have demonstrated nearly qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 16 publications
2
45
0
Order By: Relevance
“…The use of amino acids with hydrophilic (polar or charged) side chains in the N-terminal chelators provided reduced liver uptake and low levels of hepatobiliary excretion (14,(16)(17)(18)22), whereas the composition of the C-terminus was shown to be less influential in that aspect (23). However, in agreement with previously published data on chelator stability and biodistribution of 99m Tc-labeled proteins (24)(25)(26), the use of an N 3 S cysteine-based chelator at the C-terminus provided appreciably less release of 99m Tc-pertechnetate in the circulation than did the SN 3 chelator at the N-terminus (15,19,21). Furthermore, Ala 1 ,Glu 2 at the N-terminus has been shown to be associated with low hepatic uptake and low hepatobiliary excretion (19,(21)(22)(23).…”
supporting
confidence: 78%
“…The use of amino acids with hydrophilic (polar or charged) side chains in the N-terminal chelators provided reduced liver uptake and low levels of hepatobiliary excretion (14,(16)(17)(18)22), whereas the composition of the C-terminus was shown to be less influential in that aspect (23). However, in agreement with previously published data on chelator stability and biodistribution of 99m Tc-labeled proteins (24)(25)(26), the use of an N 3 S cysteine-based chelator at the C-terminus provided appreciably less release of 99m Tc-pertechnetate in the circulation than did the SN 3 chelator at the N-terminus (15,19,21). Furthermore, Ala 1 ,Glu 2 at the N-terminus has been shown to be associated with low hepatic uptake and low hepatobiliary excretion (19,(21)(22)(23).…”
supporting
confidence: 78%
“…The labeling efficiency (Table 2) was 53.8 ( 10.1%, which is lower than obtained for maGGG-containing Z HER2:342 conjugate (about 80%) (22). George and co-workers (24) have reported that labeling of scFv containing the GGGC sequence provided higher labeling yields (about 97%) in an alkaline condition. Alkaline pH is usually favorable for rapid 99m Tc-labeling, probably because of deprotonation of sulfur and nitrogen donor atoms, which facilitates the complexation of technetium (35,36).…”
Section: Discussionmentioning
confidence: 94%
“…For recombinant production, which would be required in this case, an incorporation of synthetic chelators would be possible only as a separate process. A possible alternative has been proposed earlier for scFv (24)(25)(26), namely an incorporation of a terminal cysteine, which would form N3S chelator together with adjacent amino acids. Still, we had to take into account that direct translation of a labeling technique from one protein to another is not easy in the case of technetium, since the surrounding amino acids influence the stability of the chelate on one hand, and the chelator may affect the biodistribution properties of a targeting protein on the other (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical biosensor technology has been increasingly used to study molecular interactions [15,16], but almost all of these studies have involved plasmon resonance biosensors (BIAcore; Pharmacia). More recently, the resonant mirror bisensor [21,23] has been used to study the affinity of anti-saporin antibodies [20], and the kinetics of recombinant single-chain Fv binding to their antigens [24]. George et al have also been able to use the IAsys biosensor to detect and quantify the presence of human anti-mouse antibodies in the sera of patients treated with murine MoAbs [25].…”
Section: Discussionmentioning
confidence: 99%